2015
DOI: 10.1007/s10965-015-0794-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyvinyl alcohol/chitosan hydrogel compounded with graphene oxide to enhance the adsorption properties for Cu(II) in aqueous solution

Abstract: A novel bio-adsorbent, composite hydrogel beads, composed of polyvinyl alcohol (PVA), chitosan (CS) and graphene oxide (GO) was prepared by an instantaneous gelation method. The micromorphology and thermal stability of the PVA/CS/GO hydrogel beads were characterized by scanning electronic microscope (SEM) and thermo gravimetric analysis (TGA) respectively. Adsorption of Cu(II) onto PVA/CS/GO hydrogel beads was investigated with respect to pH, initial concentration, temperature and adsorption time. Adsorption d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 45 publications
(40 reference statements)
0
17
0
Order By: Relevance
“…It was observed that the equilibrium adsorption capacity slightly decreases after each regeneration cycle. This result is due to some active sites on CMC‐g‐AMPS hydrogel being occupied by heavy metal ions, which could not be completely recovered by desorption . Figure shows desorption ratios of 97.23 ± 0.46%, 95.69 ± 0.32% and 96.54 ± 0.19% for the first adsorption–desorption cycle of Cu 2+ , Pb 2+ and Fe 3+ ions, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…It was observed that the equilibrium adsorption capacity slightly decreases after each regeneration cycle. This result is due to some active sites on CMC‐g‐AMPS hydrogel being occupied by heavy metal ions, which could not be completely recovered by desorption . Figure shows desorption ratios of 97.23 ± 0.46%, 95.69 ± 0.32% and 96.54 ± 0.19% for the first adsorption–desorption cycle of Cu 2+ , Pb 2+ and Fe 3+ ions, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Graphene as the nanoadsorbent mainly includes three forms: pristine graphene, graphene oxide (GO), and reduced graphene oxide (rGO) [58]. GO is an oxidized form of graphene, containing various oxygen-containing groups, such as epoxide, carbonyl, carboxyl, and hydroxyl groups [59][60][61][62][63]. Since the oxygen groups break the double bonds holding the carbon atoms together, GO loses its electrical conductivity.…”
Section: Graphene-based Nanoadsorbentsmentioning
confidence: 99%
“…For example, Rodrigues and co‐workers fabricated PAA–CS–GO hydrogels by first dissolving PAA and CS solution and then mixing GO dispersions. Chen and co‐workers also fabricated PVA–CS–GO hydrogels by utilizing a similar method.…”
Section: The Preparation Of Polymer–graphene Hydrogelsmentioning
confidence: 99%
“…Another kind of polymer–GO hydrogels have the ability to absorb heavy metal ions. For example, Chen and co‐workers prepared PVA–CS–GO hydrogel, which can absorb Cu 2+ . Wang and co‐workers prepared a series of cross‐linked sodium acrylate and acrylamide copolymer/graphene oxide hydrogels, which can be used as the adsorbent for systematic adsorption of Pb 2+ and Cd 2+ from aqueous solutions.…”
Section: Properties and Applications Of Polymer–graphene Hydrogelsmentioning
confidence: 99%